Investigation of laminar separation bubble over a supercritical airfoil in an incompressible flow. (February 2022) - Tatar, Massoud; Masdari, Mehran; Tahani, Mojtaba
Supercritical airfoils have an unknown behavior at incompressible flow regime and Reynolds numbers lower than those related to their design point at transonic condition. In this work, boundary layer transition is studied over a supercritical airfoil by means of hot-film and pressure measurements completed with numerical simulations. The experiments are performed at chord-based Reynolds number of8.11   ×   10 5   and Mach number of0.1 at different angles of attack. Hot-film measurement over the upper surface of the supercritical airfoil is carried out and the transition points are computed using the standard deviation of the signals. The upper surface pressure is also recorded and a peak in its second derivative is presented as the transition point generated by the laminar separation bubble mechanism. Moreover, an appropriate time-frequency analysis is applied to the hot-film signals to get an insight into the spectral content and development of the transitional boundary layer structures. On the other hand, two numerical codes are employed and the transition points obtained from numerical simulations are compared with the experimental outcomes. Results express a rapid change of the bubble position over the upper surface, as the angle of attack is increased to the value of2 ° . Laminar separation bubble is observed in the surface pressure distribution data and is well identified using its second derivative along the streamwise direction. The spectral characteristics of the boundary layer are satisfactorily explored including the streamwise fluctuations within the laminar flow, intermittent behavior of the transitional zone and the wide range of the spectrum in turbulent flow, thanks to the time-frequency analysis. A promising agreement is observed between the transition points computed by both the numerical and experimental studies and confirms the accuracy of findings achieved by the second derivative of surface pressure data, hot-film measurements and the reliability of the employed numerical transition models for optimization studies.